PTH-102 Cirrhotic patients with vitamin D deficiency fail to respond to oral replacement therapy. (8th June 2018) - Rhodes, Freya; Greenham, Olivia; Hunt, Emma; Shah, Tina; Patch, David; Ryan, Jennifer; Westbrook, Rachel
Abstract : Introduction: Vitamin D deficiency and reduced BMD are highly prevalent in patients with advanced chronic liver disease. For bisphosphonate treatment for osteoporosis to be effective vitamin D levels must be replete. Moreover, vitamin D deficiency has been associated with an increased risk of infections and increased rejection rates following liver transplantation. The optimal dose and route of vitamin D replacement in cirrhosis is unknown. BSG guidance currently recommends 800 IU/day orally for all patients with cirrhosis/cholestatic liver disease. Methods: Retrospective review of 218 cirrhotic patients undergoing evaluation for liver transplant between 2016 and 2017. Vitamin D 'severe deficiency' was defined as <25 ng/ml, 'deficiency' 25–50 ng/ml and normal >50 ng/ml. Response to oral vitamin D therapy was recorded. Results: Out of 218 patients, 128/218 (59%) had low Vitamin D levels with 25% (n=55) 'severely deficient' and 33% (n=73) 'deficient'. Overall 33 patients with levels<50 ng/ml (52%), and 31 patients (48%) with levels>50 ng/ml received replacement therapy. (p=0.86) Median daily dose of Vitamin D replacement was 2800 units/day (IQR 800–2800) in <25 ng/ml group, 2860 units/day (IQR 800–2800) in <50 ng/ml group and 800 units/day (IQR 800–2000) in >50 ng/dl group. No significant difference in dosing between these groups (p=0.12). Data on vitamin D levels pre and post 3 months of treatment with Vitamin D therapy were available in 58 patients. Patients received either 400IU/day (n=6), 800–1600IU/day (n=28) or >1600 IU/Day (n=24). Median delta change in vitamins D levels in the 3 groups were −3 ng/ml, −1 ng/ml and 12 ng/ml over the 3 month treatment period. An average daily dose of >1600 IU/day Resulted in a significantly greater increase in Vitamin D levels when compared to doses<1600 IU/day (p=0.01), albeit still sub optimal with only a median increase of 12 ng/ml. When those patients with Vitamin D levels of <50 ng/ml were reviewed in isolation (n=29), 82% failed to augment vitamin D levels to within the normal range >50 ng/dl and no significant difference was found between dosages of vitamin D administered. Conclusion: Vitamin D deficiency is prevalent, affecting over 50% of patients with advanced cirrhosis. Oral vitamin D replacement therapy is ineffective in cirrhotics at repleting stores over a 3 month period irrespective of dose given. Future evaluation of efficacy of IM administration in this unique cohort of patients is urgently needed to evaluate if this allows normalisation of Vitamin D levels.